The Limit of the Stefan Problem with Surface Tension and Kinetic Undercooling on the Free Boundary (Journal of Partial Differential Equations, 1996)
In this paper we consider the Stefan problem with surface tension and kinetic undercooling effects, that is with the temperature u satisfying the condition u = -σK - εV_n on the interface Γ_t, σ, ε = const. ≥ 0 where K and V_n are the mean curvature and the normal velocity of Γ_t, respectively. In any of the following situations: (1) σ > 0 fixed, ε > 0, (2) σ = ε → 0; (3) σ → 0, ε = 0, we shall prove the convergence of the corresponding local (in time) classical solution of the Stefan problem.
Keywords: Limit; Stefan problem; lower order terms; model problem; Fréchet derivative